The Effect of Financial Ratio and Interest Rate of Bank on Working Capital Loan Distribution (Study on Commercial Banks Listed in The Indonesia Stock Exchange for The Period 2017 – 2021) - Dwi Dewianawati; Fajar Purwanto; Erry Setiawan (PT FORMOSA CENDEKIA GLOBAL, 2022)
Banking has a major role in the economy to raise funds from the public which is then channeled back to the community in the form of credit. Not optimal lending conducted by the bank into the background of this study. For that we need to be determined how financial ratios, and the bank rate on loans for working capital. The data used in this research is secondary data where the population used in this study is a commercial bank listed on the Indonesia Stock Exchange in the period 2017-2021. Purposive sampling method, so that from 40 companies acquired a total of 14 banks as samples. The analytical method used in this research is multiple linear regression. Partial results of this study show that the LDR and ROA significantly and negatively related to working capital lending. CAR positive and significant impact on working capital lending, while interest rates don’t affect the working capital loan portfolio. And simultaneously shows that LDR, CAR, ROA and interest rates significant positive effect on working capital loans.